Investigation of valley-resolved transmission through gate defined graphene carrier guiders. (1st March 2017) - Cao, Shi-Min; Zhou, Jiao-Jiao; Wei, Xuan; Cheng, Shu-Guang
Abstract: Massless charge carriers in gate potentials modulate graphene quantum well transport in the same way that a electromagnetic wave propagates in optical fibers. A recent experiment by Kim et al (2016 Nat. Phys .12 1022 ) reports valley symmetry preserved transport in a graphene carrier guider. Based on a tight-binding model, the valley-resolved transport coefficients are calculated with the method of scattering matrix theory. For a straight potential well, valley-resolved conductance is quantized with a value of 2 n + 1 and multiplied by 2 e 2 / h with integer n . In the absence of disorder, intervalley scattering, only occurring at both ends of the potential well, is weak. The propagating modes inside the potential well are analyzed with the help of band structure and wave function distribution. The conductance is better preserved for a longer carrier guider. The quantized conductance is barely affected by the boundaries of different types or slightly changing the orientation of the carrier guider. For a curved model, the state with momentum closes to the neutral point is more fragile to boundary scattering and the quantized conductance is ruined as well.